Structure of a new glycyrrhiza polysaccharide and its immunomodulatory activity - Wu, Yu; Zhou, Hui; Wei, Kunhua; Zhang, Tao; Che, Yanyun; Nguyễn, Audrey D.; Pandita, Sakshi; Wan, Xin; Cui, Xuejie; Zhou, Bingxue; Li, Caiyue; Hao, Ping; et al. (Frontiers in Immunology, 2022)
A new component of Glycyrrhiza polysaccharides (GPS-1) was extracted from licorice, and its primary structure and immunomodulatory activity were studied. Crude licorice polysaccharide was isolated and purified by DEAE sepharose FF ion-exchange column chromatography and Chromdex 200 PG gel filtration column chromatography to obtain a purified Glycyrrhiza polysaccharide named GPS-1. NMR and methylation analysis revealed that GPS-1 is composed of homogalacturonan (HG)-type pectin with 4)-D-GalpA-(1 as the backbone. This study of GPS-1 also examined its significant role in regulating immune activity in vitro and in vivo. As a result, GPS-1 promoted the secretion of IFN-γ and IL-4 in mice and increased the proportion of CD3+CD4+ and CD3+CD8+ T lymphocytes in their spleens. Dendritic cells (DCs) treated with GPS-1 showed promotion of DC maturation, antigen presentation, and phagocytic capacity. The results suggest that GPS-1 is a potential immunomodulator that stimulates the immune system by regulating multiple signaling pathways. Combined with our characterization of the primary structure of GPS-1, the present investigation provides the basis for future study of the form-function relationship of polysaccharides.